Isolated Diffuse Episcleral Neurofibroma. (April 2013) - Mohyudin, Mohamed Naeem; Darrad, Misha; Murray, Aidan; Thaung, Caroline
Abstract Aims: To report a rare case of isolated diffuse episcleral neurofibroma and to discuss possible differential diagnoses. Case report: A 37 year old Caucasian female was found to have an epibulbar tumour arising from the superior aspect of her left eye. Clinical examination revealed a 12 mm × 8 mm "salmon pink" coloured lesion. Results: A biopsy was performed and histopathologic examination and subsequent systemic evaluation showed it to be a rare case of isolated diffuse episcleral neurofibroma. Conclusion: There are many differential diagnoses for an epibulbar lesion and neurofibroma should be added to these. Even though a small risk of malignant transformation exists, we recommend a conservative approach for slow growing lesions.